Potensi Pelelangan Ikan di Kabupaten Barru Sebagai Upaya dalam Mendorong Pertumbuhan Ekonomi Maritim - Arvito Amar; Imam Fadhil Nugraha (Journal of Creative Student Research, 2024)
Fish auctions are an economic activity that has great potential in encouraging maritime economic growth. A fish auctions is the buying and selling of fish and marine products located at the port or fishing pier. Barru Regency is an example of an area on South Sulawesi Island that has enormous maritime potential because of itds large and abundant marine resources. In this case, the Barru Regency Government is trying to encourage maritime economic growth by establishing strategic policies to encourage maritime economic growth, one of which is the fish auction site, as a potential locations for the maritime economy growth. With the majority of its population being fishermen, Barru Regency certainly has several fish auction locations spread across various points as objects of maritime economic growth.